THE DEVELOPMENT OF INTERACTIVE MULTIMEDIA LEARNING MEDIA ON CELL MATERIALS IN CLASS XI IPA SMA NEGERI 2 KABANJAHE - Nadia Br Ginting; Hudson Sidabutar (ISER (Indonesian Science Education Research), 2023)
This study aims to develop and produce interactive multimedia-based biology learning media using a valid, practical and effective powerpoint media that can be applied as a biology learning medium on cell material. The type of research used is development research with a 4-D development model. This model includes four stages, namely defining, designing, developing and disseminating. The learning media developed were validated by media experts and material experts, the responses of biology teachers and responses by students in class XI PA SMA Negeri 2 Kabanjahe. All data were obtained from the data collection instrument and analyzed descriptively. The results showed: (1) The validity of the media based on the assessment of media experts and material experts by getting an average percentage of 85.5% with the criteria of "very valid / very good". (2) The practicality of learning media based on student and teacher responses after using the media got an average percentage of 95.3% which included the "very practical" criteria. (3) The effectiveness of the media based on the results of student learning mastery after using interactive multimedia learning media is 86.1%. Then the calculation of the significance level is carried out with the ngain test score . From the results of manual calculations obtained n-gain score of 0.52. Based on the results of the study, the use of interactive multimedia learning media is said to be feasible with valid, practical and effective categories.